Survival Migration Failed Governance and the Crisis of Displacement - Betts, Alexander (Cornell University Press, 2013)
Such threats as environmental change, food insecurity, and generalized violence force massive numbers of people to flee states that are unable or unwilling to ensure their basic rights, as do conditions in failed and fragile states that make possible human rights deprivations. Because these reasons do not meet the legal understanding of persecution, the victims of these circumstances are not usually recognized as "refugees," preventing current institutions from ensuring their protection. In this book, Alexander Betts develops the concept of "survival migration" to highlight the crisis in which these people find themselves.